Histopathological spectrum of cervical biopsies – a 5 year retrospective study - Dr Kanya Kumari; Dr Umarani M K; Dr Bharathi M (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: cervix is a gateway to numerous non neoplastic and neoplastic gynecological lesions. Cervical cancer is the leading cancer in Indian women and second most common cancer in women worldwide next to breast cancer. Objectives: 1) To study the histopathological features of cervical lesions. 2) To study the age distribution and relative frequency of various cervical lesions. Materials and Methods: This is 5 years retrospective study of all cervical biopsies received from 2011-2015 in the department of pathology. Result: In a total of 739 cases studied 365(49.39%) cases were non neoplastic, 113(15.29%) were pre invasive and 261(35.31%) cases were malignant. Cervicitis was the most common non neoplastic lesion and squamous cell carcinoma was the most common cancer. Conclusion: Adequate cervical screening procedure with follow up cervical biopsies helps in early diagnosis and management of premalignant and malignant lesions.